KECENDERUNGAN POLA DAN DAMPAK MIGRASI PENDUDUK DI PROVINSI BALI PERIODE 1980-2005* - Sudibia, I Ketut (PIRAMIDA; Vol. 7, No. 2 Desember 2011, 2012)
The objective of this study are to know (1) the population migration pattern in theProvince of Bali during the period 1980 to 2005; (2) the main stream of the populationmigration in the Province of Bali during the period 1980 to 1990; and (3) the impact ofpopulation migration on the economic and social life in the Province of Bali. The resultof this study will be expected not only for academic but also for practice purposes.All of data that were used for this study was obtained from the Central Board ofStatistic of the Province of Bali, the Development Planning Board of the Province ofBali, and other publications related to this study. The most important data that wereanalyzed for this study was migration data, especially lifetime migration and recentmigration. Then, the technique of analysis that were used for this study was descriptivelyby using cross tabulation.Some findings from this study are as follows: (1) The lifetime in-migrationpatterns before and after Reformation Era are still relatively the same, and dominantlydetermined by the in-migrants from East Java. But, on the other hand the lifetime outmigrationpatterns from Bali are dominantly determined by the out-migrants to someplaces of destination of transmigration program. (2) The recent in-migration pattern fromone to another periods are almost the same, a big partly of them come from East Java. Onthe contrary, the recent out-migration pattern are not having the same pattern from one toanother period. With the exception of 1980, the recent out-migration patterns from Baliare not dominantly determined by the transmigration program, but a big partly of themalso go to East Java. (3) The main stream of lifetime migration until the year 2000 is stilldescribed by the transmigration program. (4) Since the year 1990, the main stream ofrecent migration has shown a positive sign, and then its become higher until the year2005. (5) The impact of the increasing of in-migration to Bali are increasing (a) theavailable of the migrant workers with the cheaper wage; (b) the population density; (c)the informal sector; (d) the unemployment (e) slum area and environment degradation;and (f) some cases of criminality.
Keywords: lifetime and recent migration, main stream of migration, migration impact